A general strategy to add diversity to ruthenium arene complexes with bioactive organic compounds via a coordinated (4-hydroxyphenyl)diphenylphosphine ligand. Issue 36 (19th June 2017) - Biancalana, Lorenzo; Batchelor, Lucinda K.; De Palo, Alice; Zacchini, Stefano; Pampaloni, Guido; Dyson, Paul J.; Marchetti, Fabio
Abstract : Ruthenium arene complexes obtained by direct esterification of a phosphine ligand with bioactive carboxylic acids show enhanced cytotoxicity compared to the respective precursors. Abstract : Esterification of (4-hydroxyphenyl)diphenylphosphine, coordinated to the [Ru(η 6 - p -cymene)Cl2 ] fragment, allows a series of bioactive carboxylic acids to be introduced directly into the organometallic molecule. Evaluation of the compounds on human ovarian cancer cells reveals synergistic enhancements in their antiproliferative activity relative to their bioactive organic and organometallic precursors.